2020
DOI: 10.1093/database/baaa038
|View full text |Cite
|
Sign up to set email alerts
|

RGPDB: database of root-associated genes and promoters in maize, soybean, and sorghum

Abstract: Root-associated genes play an important role in plants. Despite the fact that there have been studies on root biology, information on genes that are specifically expressed or upregulated in roots is poorly collected. There exist very few databases dedicated to genes and promoters associated with root biology, preventing effective root-related studies. Therefore, we analyzed multiple types of omics data to identify root-associated genes in maize, soybean, and sorghum and constructed a comprehensive online datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Therefore, a more targeted exploration of Tabula Glycine might reveal additional interesting cell-type marker candidate genes. As another reflection of the uses of Tabula Glycine, we also reevaluated the expression pattern of 318 soybean genes identified as preferentially expressed in the soybean root system [44]. While we confirmed the preferential activity of these genes in the root and the nodule, we noticed their differential expression between clusters (Figs.…”
Section: Evaluating the Transcriptomic Heterogeneity Of The Soybean C...mentioning
confidence: 73%
“…Therefore, a more targeted exploration of Tabula Glycine might reveal additional interesting cell-type marker candidate genes. As another reflection of the uses of Tabula Glycine, we also reevaluated the expression pattern of 318 soybean genes identified as preferentially expressed in the soybean root system [44]. While we confirmed the preferential activity of these genes in the root and the nodule, we noticed their differential expression between clusters (Figs.…”
Section: Evaluating the Transcriptomic Heterogeneity Of The Soybean C...mentioning
confidence: 73%
“…To verify the accuracy of all the tissue-specific genes, we conducted a comprehensive literature search and finally collected 2,108, 1,908, 1,516, and 2,122 tissue-specific genes in total for leaf, root, seed, and nodule, respectively ( Supplementary File 2 ), which are used as the benchmark datasets ( Libault et al, 2009 , 2010 ; Severin et al, 2010 ; Asakura et al, 2012 ; Jones and Vodkin, 2013 ; Brown and Hudson, 2015 ; Machado et al, 2020 ; Moisseyev et al, 2020 ). Supplementary Figure 6 shows the common genes between our results (denoted as O) and genes found in the eight benchmark studies (from A to H, with some detailed information from each study shown in Supplementary File 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many efficient technologies have been developed in plants based on the superposition of modular cloning systems with predefined standardization. TDTHub A web server tool for the analysis of transcription factor binding sited in plants [23] PPDB A web-based plant promoter database [24] PlantCARE A database of plant cis-acting regulatory elements, enhancers and repressors [25] OptoBase An online platform for molecular optogenetics [26] TRANSFAC A database on eukaryotic transcription factors [27] RGPDB A database of root-associated genes and promoters in maize, soybean, and sorghum [28] TSSFinder A tool for prediction and annotation of different organisms [29] PlantProm A database of plant promoter sequences [30] TSSP Prediction of plant promoters [31] NSITE-PL Recognition of plant regulatory motifs [32] AGRIS The Arabidopsis gene regulatory information server [33] AthaMap A genome-wide map of putative transcription factor binding sites in Arabidopsis thaliana [34] multiple gene cassettes [61]. Building on the standard Type IIS syntax, jStack leverages in vivo yeast homologous recombination to assemble large DNA fragments, such as multiple gene expression cassettes, into plant transformation vectors by one-pot [62].…”
Section: Standardized Assemblymentioning
confidence: 99%